## Solving the Equation (x + 15)² = 6

This equation involves a squared term, which means we need to use the square root property to solve for *x*. Here's how:

### 1. Isolate the Squared Term

Begin by isolating the squared term on one side of the equation. In this case, it's already isolated:

**(x + 15)² = 6**

### 2. Take the Square Root of Both Sides

Take the square root of both sides of the equation. Remember that taking the square root results in both positive and negative solutions:

**√(x + 15)² = ±√6**

This simplifies to:

**x + 15 = ±√6**

### 3. Solve for x

Now, isolate *x* by subtracting 15 from both sides:

**x = -15 ±√6**

### 4. Simplify the Solution

We now have two possible solutions:

**x = -15 + √6****x = -15 - √6**

These are the exact solutions. You can approximate them to decimal form if needed.

**Therefore, the solutions to the equation (x + 15)² = 6 are x = -15 + √6 and x = -15 - √6.**